Circularly polarize antenna array for electromagnetic energy harvesting - Chao Kang, Chia; Yang Kang, Chia (International Journal of Engineering and Technology, 2018)
Electromagnetic energy harvesting from ambient sources have been presented more than 50 years. In this paper, electromagnetic energy harvesting by using circular polarize antenna array is presented. The proposed antenna is having 2 similar size of spiral inductor that feed by microstrip feed line. The gain, momentum visualization were investigated. The circular polarize antenna are fabricated on Roger 4003 substrates. Based on the observations, it is expected that the gain obtained by the antenna array is higher than the single element antenna. The simulation results show that 3.22 dBi gain can be achieved for single spiral antenna whereas the antenna array can achieved as high as 5.14dBi at frequency 527MHz. The work concluded that investigations of electromagnetic energy harvesting antenna array is successful.Â